2019
DOI: 10.1177/1460458219892162
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of physicians’ satisfaction with telemedicine services acceptance

Abstract: Despite the significant increase in telemedicine services technology, its adoption and use have been quite slow in some healthcare settings. It is generally accepted in today’s globalizing world that the success of telemedicine services relies on users’ satisfaction. Satisfying physicians and patients is one of the crucial objectives of telemedicine success. This study seeks to evaluate physicians’ satisfaction with telemedicine services adoption and utilization using the technology acceptance model. A structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 59 publications
11
101
1
3
Order By: Relevance
“…Overall, based on the respondents' characteristics, we can argue that our sample can represent populations most likely to benefit from electronic health exchange. According to the United States Census Bureau, 63 women represent just under 51% of the U.S. population, and it is consistent with our sample. Regarding age distribution, the main difference between our sample and the U.S. population is people 60 years and older, in which our sample shows 6.18% compared with the U.S. population, which is 16.5%.…”
Section: Generalizability Of Resultssupporting
confidence: 90%
“…Overall, based on the respondents' characteristics, we can argue that our sample can represent populations most likely to benefit from electronic health exchange. According to the United States Census Bureau, 63 women represent just under 51% of the U.S. population, and it is consistent with our sample. Regarding age distribution, the main difference between our sample and the U.S. population is people 60 years and older, in which our sample shows 6.18% compared with the U.S. population, which is 16.5%.…”
Section: Generalizability Of Resultssupporting
confidence: 90%
“…Notably rapid expansion of telemedicine visits for physicians was aided by having appropriate support staff to contact patients and coordinate visits. Incorporating telemedicine into existing workflow may reduce clinician burden and has been a reported predictor of physician acceptance 15 . There are recognized limitations in telemedicine for performing aspects of the physical examination, 11 although recent solutions have been proposed to improve this aspect of care 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The observation that desire to continue offering telemedicine visits after the COVID-19 pandemic correlates not only with confidence with the examination and satisfaction with the modality, 22 but also with personal factors such as belief that adaptability is an important element of being a clinician, clinicians who identify as being more perceiving (value flexibility) than judging (value organization), and less preference for in-person work meetings over virtual meetings suggests that clinicians who are going to have less preference for telemedicine going forward can be identified by other traits and preferences. In the qualitative interviews along with our personal observations and interactions, including prior investigations, 23,24 we found that both clinicians and patient concerns about telemedicine are things that lessen after a good telemedicine experience.…”
Section: Discussionmentioning
confidence: 99%